The Profitability of the Hungarian Agriculture Against the Back-groundof the European Union. - Rajczi, Alexandra; Wickert, Irén (Acta Scientiarum Socialium, 2015)
Hungary’s agriculture has a thousand-year-old history; our natural conditions are more favourable than average, thus they ensure an acceptable quality and an optimal quantity of yields. After the political and economic transition, however, this endowment has not proved to be sufficient for the Hungarian agriculture to be able to keep up with the growing trends in the European countries. During the decades following the transition Hungary’s agriculture was focused on the issues of restitution and the restructuring of agricultural cooperatives. In this period the Hungarian agriculture was more and more characterised by undersized farms and this structure determines the agriculture even today. Government policies have taken several measures to mitigate this so that the evolved farm sizes can strengthen and compete with other European countries. Since Hungary’s accession to the EU in 2004 the Hungarian agricultural branches have received CAP subsidies. The subsidies not only influence the profitability of particular branches but also determine their structure. Since our accession Hungary’s agriculture has received almost 3 430 billion forints subsidies.
Keywords: agriculture; profitability; (non-repayable) grants; CAP; European Union; political and economic transition